Red rabbit - Clancy, Tom, 1947-2013. (New York : Berkley Books, 2003)
In the early days of his career, Jack Ryan accepts a first assignment as freelance analyst under James Greer of the CIA and faces a mission involving a high-level Soviet defector who has reported a plot to assassinate Pope John Paul II.
Keywords: Ryan, Jack, -- Sr. (Fictitious character) -- Fiction; John Paul -- II, -- Pope, -- 1920-2005 -- Assassination attempts -- Fiction; Attempted assassination -- Fiction; Intelligence officers -- Fiction; Americans -- England -- Fiction; Popes -- Fiction; Political fiction; Suspense fiction